Kerusakan Kerusakan Bangunan Rumah Tinggal (Studi Kasus: Gempa Aceh 2 juli 2013) - Muhammad Arrie Rafshanjani Amin (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2018)
Central Aceh Regency and Bener Meriah Regency of the Aceh Province is geologically located in the subduction of the Asian and Australian plate encounters, and is located at the end of Sumatra's fault / transform fault. This is what makes Aceh vulnerable to earthquake disaster. On July 2, 2013 a magnitude 6.1 earthquake shook the province of Aceh causing damage to buildings adjacent to the epicenter. Judging from the strength of the earthquake, this earthquake is one of the major earthquakes that hit Aceh. A research on the ratio of damaged house was conducted through a direct observation of spaciousness by taking samples of damaged houses for each category (collapsed, heavily damaged, moderately damaged, and lightly damaged) then an average is taken for each category of damage. The Result of research shows that the average ratio for collapsed houses are 96,25%, severe damage 70,08%, moderate damage 28,08% and light damage 3,87%, the average value of damage ratio is includes in the standard which established by Fema 1999. Keywords: Damage Ratio, Earthquakes, house damage category